The use of MFA and LCA in the agriculture waste management system in Kuala Terengganu - Ghani, Latifah Abdul; Mahmood, Noor Zalina; Ali, Nora'aini (Construction Research Institute of Malaysia, 2018)
Agricultural waste management, as practiced by the vast majority of farmers and farm owners in agricultural areas in the district of Kuala Terengganu, involves four process scenarios, namely S1: On farm burial, S2: On-farm burning, S3: Landfill and S4: Recycled. However, the disposal of agricultural waste has produced an environmental impact on the ecosystem in different ways. The aim of this study is to compare the potential environmental damage incurred from the disposal of agricultural waste in the four scenarios above. Data collection was conducted in ten farms located in Kuala Terengganu. The research includes the analysis of agricultural waste, the analysis of crop residue characteristics, and the analysis of potential contamination using the Life Cycle Assessment (LCA) approach that utilizes the Simapro software. The results showed that the scenarios S3 and S1 have resulted in a value credit for the destruction of the environment, compared to the debit value of both S2 and S4. In this study, Material Flow Analysis-Life Cycle Assessment model of integration, with Integration of Material Flow Analysis-Life Cycle Assessment, has been developed and tested based on real data to confirm their validity as a valuable tool for assessing the environmental conditions for agricultural waste management system in the study region.